Differences in risk factors for hepatitis B, hepatitis C, and human immunodeficiency virus infection by ethnicity: A large population-based cohort study in British Columbia, Canada. (May 2021) - Binka, Mawuena; Butt, Zahid Ahmad; McKee, Geoffrey; Darvishian, Maryam; Cook, Darrel; Wong, Stanley; Yu, Amanda; Alvarez, Maria; Samji, Hasina; Wong, Jason; Krajden, Mel; Janjua, Naveed Zafar
Highlights: Major risk factors for HBV, HCV, and HIV monoinfection/coinfection may differ by ethnicity. Understanding these differences will improve screening initiatives. Factors associated with infection among different ethnic groups in British Columbia were assessed. Substance use prevalence was significantly lower among visible minority ethnic groups. Where present, substance use was associated with increased risk of HBV and/or HCV and/or HIV infection. Abstract: Objectives: Addressing the needs of ethnic minorities will be key to finding undiagnosed individuals living with hepatitis B (HBV), hepatitis C (HCV), or human immunodeficiency virus (HIV). To inform screening initiatives in British Columbia (BC), Canada, the factors associated with HBV and/or HCV and/or HIV infection among different ethnic groups within a large population-based cohort were assessed. Methods: Persons diagnosed with HBV, HCV, or HIV in BC between 1990 and 2015 were grouped as East Asian, South Asian, Other Visible Minority (African, Central Asian, Latin American, Pacific Islander, West Asian, unknown ethnicity), and Not a Visible Minority, using a validated name-recognition software. Factors associated with infection within each ethnic group were assessed with multivariable multinomial logistic regression models. Results: Participants included 202 521 East Asians, 126 070 South Asians, 65 210 Other Visible Minorities, and 1 291 561 people who were Not a Visible Minority, 14.4%, 3.3%, 4.5%, and 6.3% of whom had HBV and/or HCV and/or HIV infections, respectively. Injection drug use was most prevalent among infection-positive people who were Not a Visible Minority (22.1%), and was strongly associated with HCV monoinfection, HBV/HCV coinfection, and HCV/HIV coinfection, but not with HBV monoinfection among visible ethnic minorities. Extreme material deprivation and social deprivation were more prevalent than injection drug use or problematic alcohol use among visible ethnic minorities. Conclusions: Risk factor distributions varied among persons diagnosed with HBV and/or HCV and/or HIV of differing ethnic backgrounds, with lower substance use prevalence among visible minority populations. This highlights the need for tailored approaches to infection screening among different ethnic groups.